2019
DOI: 10.1080/10376178.2019.1657359
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the challenges posed by an escalating diabetes healthcare burden: A mixed methods study

Abstract: Aims and objectives: To identify innovative new strategies to maintain optimal care for patients with diabetes while in hospital. Background: The ongoing escalation in the incidence of diabetes is contributing to a growing burden associated with diabetes management. Design: Mixed methods underpinned by Appreciative Inquiry. Methods: Online survey (n=173) and focus group interviews with nurses and midwives (n=40), and individual interviews with recently discharged hospital patients (n=6). Results: Suggest a nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The increasing prevalence of diabetes is a public health problem and growing economic burden worldwide (Atsalos et al, 2019), causing long‐term and devastating complications such as blindness, stroke, renal failure or cardiovascular disease (American Diabetes Association, 2021b). Metabolic control is indicated by glycosylated haemoglobin (HbA1c) levels and has a strong predictive value for diabetes complications.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing prevalence of diabetes is a public health problem and growing economic burden worldwide (Atsalos et al, 2019), causing long‐term and devastating complications such as blindness, stroke, renal failure or cardiovascular disease (American Diabetes Association, 2021b). Metabolic control is indicated by glycosylated haemoglobin (HbA1c) levels and has a strong predictive value for diabetes complications.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 19 studies analysed, 13 studies reported on the (1) effects of IPE/IPC on provider or student characteristics in diabetes care provision and (2) on aspects of healthcare provision for patients with diabetes that were impacted. For provider/student characteristics, the studies mention advancements in self-perceived competence in diabetes care [17], improved confidence [17,21,24], knowledge [21,23,24,27], skills [23,24], behaviour [23,26] and attitudes [20,24] toward IPE and collaborative practice. For modified aspects of healthcare, the studies report improved clinical practice [9,17,26,31], quality of care [23,26,29,32], understanding of roles and responsibilities of other HCPs or students [20,28], communication [7,21,28], collaboration and interprofessional team care [7,21,27] and provider productivity [7].…”
Section: Impact On Provider/student Approaches and Enhancement Of Car...mentioning
confidence: 99%
“…Better self-perceived competence in diabetes care [17] Improved confidence [17,21,24] Improved knowledge [21,23,24,27] Improved skills [23,24] Improved behaviour [23,26] Improved attitudes toward IPE and IPC [35] Impact on aspects of healthcare provision Improved clinical practice [9,17,26,31] Improved quality of care [23,26,29,32] Improved understanding of roles and responsibilities of other HCPs or students [20,28] Improved communication [7,21,28] Improved IPC and team care [7,21,27] Improved provider productivity [7] 3.6. Effect on Diabetes Self-Management and Disease Outcomes…”
Section: Reported Parameter Selected Studiesmentioning
confidence: 99%
“…They have a major effect when supporting patients with self-management of their condition particularly using the proactive care management model and decision making support approaches [18][19][20][21][22]. Numerous studies outside SSA [16, [23][24][25][26][27] and within Africa [28][29][30][31][32][33][34][35] report low knowledge levels of diabetes and diabetes care among nurses. However, the factors that hinder and promote the nurses' acquisition of diabetes knowledge are not well established.…”
Section: Introductionmentioning
confidence: 99%